Error-feedback temperature regulation for a reverse flow reactor driven by a distributed parameter exosystem. (September 2022) - Aksikas, Ilyasse
Abstract: This work is devoted to solve the state and error-feedback control problems for a catalytic reverse flow reactor (CFRR), which is modeled by nonlinear partial differential equations (PDEs). These two regulation problems will be solved based on the linearized infinite-dimensional representation. The objective is to track a desired output reference under the presence of disturbances. Both the reference trajectory and the disturbance profiles are generated by a distributed parameter exosystem. First, a state feedback stabilizing regulator is designed which drives the process output to a reference trajectory. The second main aim is to develop a dynamical controller that uses the tracking error as an input. Furthermore, it has been demonstrated that the closed-loop plant is exponentially stable and the tracking error asymptotically goes to zero. The developed regulators are evaluated through numerical simulations for the case study of methane combustion. Highlights: Description of the reverse flow reactor by PDEs model with its infinite-dimensional representation. Design of a state-feedback regulator for the CFRR model under the presence of distributed disturbances. Design of an error-feedback regulator for the CFRR model under the presence of distributed disturbances. Test the performances of the designed regulators through numerical simulations for methane combustion.